FIQIH IBADAH VERSUS FIQIH MUAMALAH - Fathul Aminudin Aziz (Fakultas Ekonomi dan Bisnis Islam (FEBI), Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2019)
People's understanding of fiqh of worship is only a matter for the happiness of the hereafter while understanding muamalah fiqh / Economy is for world happiness only. Understanding like this will have an impact on the radical behavior of Muslims, which is hard behavior and considers the separation absolutely necessary. Whereas in other propositions there are still many criteria for the process of worship to find happiness in the hereafter such as intention. Intention will determine whether an action is good or not good, right or wrong and there are many more propositions that make someone happy in the world and the hereafter. The muamalah fiqh in this paper is limited to economic studies, in order to focus more closely on the extent of muamalah studies. This limitation is only an example, because the essence of muamalah is not an example, but rather the construction of the proposition. Separation of world affairs and the hereafter on the other hand also has an impact on lagging in world civilization. Technology that is always changing and developing all the time cannot be balanced by some Muslims except as connoisseurs of technology. The emergence of new technology actually triggers inequality in society, and its inability to conclude that it is not important because of world affairs, unfortunately our helplessness when Muslims feel very left behind in technology actually triggers the separation of world science and the hereafter, and the choice is to build hatred that triggers the emergence of the movement radical behavior. No longer heard the movement of a creative generation of young Muslims, gradually vanished eroded by the logic of looking for happiness in the hereafter by leaving world activities. The reality that occurs is precisely concerning the younger generation of Islam, even they are sometimes willing to sacrifice themselves to find happiness in the hereafter with suicide bombings using the logic of jihad. Data from the Wahid Institute in 2016 showed that 7.7% of Indonesians claimed to be willing to participate, and 0.4% had participated in activities that could potentially cause violence in the name of religion, while 72% disagreed with radicals.